2012
DOI: 10.1002/jor.22260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selective paralysis of the supraspinatus muscle using botulinum neurotoxin a in rotator cuff healing in rats

Abstract: We hypothesized that a temporary rotator cuff paralysis using botulinum-neurotoxin A (BoNtA) would lead to an improved tendon-to-bone healing after repair of supraspinatus lesions. One hundred sixty Sprague-Dawley rats were randomly assigned to either the BoNtA or the control (saline) group. BoNtA/saline-solution was injected into the supraspinatus muscle 1 week prior to surgery. A supraspinatus defect was made; we distinguished between a lesion with normal and increased repair load. Furthermore, one subgroup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The available studies, addressing BoNtA in tendon healing, all injected the drug intra-operatively although it unfolds its full effect after one week (19). We were already able to demonstrate that preoperative BoNtA injection can positively alter tendon-to-bone healing (18). Our hypothesis in this study was that BoNtA application to the muscle influences tissue characteristics positively and might be used as a neoadjuvant prior to rotator cuff repair.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…The available studies, addressing BoNtA in tendon healing, all injected the drug intra-operatively although it unfolds its full effect after one week (19). We were already able to demonstrate that preoperative BoNtA injection can positively alter tendon-to-bone healing (18). Our hypothesis in this study was that BoNtA application to the muscle influences tissue characteristics positively and might be used as a neoadjuvant prior to rotator cuff repair.…”
Section: Introductionmentioning
confidence: 86%
“…Tissue characteristics, especially load to failure, were inferior when compared with the saline injected control group. Contrary to that observation Hettrich et al (16) and Ficklscherer et al (18) found no difference in mechanical properties but rather in collagen fiber organization.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Current research has not clearly elucidated the role of mechanical loading in the pathological shoulder joint, but also the benefits/drawbacks of post-operative immobilisation continue to be confounding. 5 Methods such as casting immobilisation, 49,55 botulinum toxin injections, 56,57 and overuse activity 51,52 have been used to alter the mechanical loads imparted upon the shoulder joint before and after surgical intervention. Results suggest that pre-operative immobilisation may have beneficial effects on long-term healing because this approach has resulted in improved cellularity and collagen organisation, while simultaneously increasing the Collagen I:Collagen III ratio, which is indicative of the end stages of tendon healing.…”
Section: Rotator Cuffmentioning
confidence: 99%